ANALISIS PENGARUH FAKTOR DEMOGRAFI DAN NORMA SUBJEKTIF TERHADAP KEPUTUSAN INVESTASI SAHAM - Tommy Prasetyo, Dewantoro; Iriani, Ade (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
Investment decisions are an alternative to increasing future income by allocating and allocating funds allocated to an activity in order to obtain profits. Selection of the right investment will bring someone in a better future planning. Individual planning for investment decisions can take the form of stock investments. This study supports to obtain empirical evidence between demographic factors and subjective norms with stock investment decisions. This research was conducted on investors who actively transact on the Indonesian stock exchange and are included as investors through a panin of securities in Semarang. A sample of 72 respondents was obtained with the margin of error (Moe) method. The analysis technique used is multiple linear regression. Based on the results of the analysis found on age, education, education and positive valuation norms on stock investment decisions. The coefficient of determination (adjusted r2) shows a value of 0.770. This shows that 77% of the dependent variable of investment decisions can be determined by the independence variables of age, education, subjective norms. While the remaining 23% is determined by variables not included in this study.